A new species of Corallana Dana, 1852 (Crustacea: Isopoda: Corallanidae) from the Andaman Islands, northern Indian Ocean - Anil, Pathan; Bruce, Niel L.; Jayaraj, K.a. (Zootaxa, 2022)
Corallana mishrai sp. nov. collected from dead mangrove roots at Kodiyaghat, South Andaman, Andaman Islands, India is described and illustrated in detail. Corallana mishrai sp. nov. the first definitive record of the genus from India, is characterized by: frontal lamina with short straight (or very weakly convex) lateral margins and the anterior margin forming a strong acute median point; pleotelson length 0.76 greatest width, posterior margin with 5 robust setae; uropodal exopod 7 times longer than greatest width, extending beyond endopod by one fourth of its length; endopod lateral margin slightly convex with 4 RS and PMS, apex forms a slightly obtuse angle with long simple setae, mesial margin weakly convex with 2 RS and PMS; mandible bidentate; transverse row of 6 tubercles present on pereonite 1 and pleonites 2, 3 and 4 lacking lateral tubercles. The status of the genus and its species are reviewed, and two species are transferred to new combinations: Argathona kulai (Bruce, 1982) comb. nov. and Tachaea bidentata (Jones et al. 1983) comb. nov.